Honorio Delgado y el psicoanálisis, 1915-1930: un estudio cuantitativo - León, Ramón (1983)
The impact of Honorio Delgado's work in the exposition of Freud's theories is studied through a quantitative approach to european and american journals between 1915 and 1930. Analysis of the data shows that Karl Abraham was the link between Delgado and psychoanalytical circles. Abraham translated an article published in spanish by the peruvian psychiatrist and commented some of his works.